Leishmania donovani promastigote: Effect of Adrenergic Agonists and Antagonist on Growth and Lipophosphoglycan Synthesis - Kar, Kalipada; Kar, Sujata (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Background: Leishmania is the causative agent of a spectrum of diseases in human ranging in severity from self-healing cutaneous form to disfiguring mucocutaneous lesion to deadly visceral form of leishmaniasis. The treatment is still suffering from toxicity of the present drug regimen and the emergence of drug resistant leishmaniasis. Successful immunotherapy is yet to develop. It is beneficial to venture the parasite second messenger systems for the development of successful antileishmanial agents. The role of adrenergic receptor agonists and antagonist in the growth of L. donovani promastigotes and the synthesis of phosphorylated macromolecules were addressed in this report. Materials and Methods: The present work is entirely experimental. The effect of dibutyryl cAMP (db-cAMP), dibutyryl cGMP (db-cGMP), epinephrine, isoproterenol and propranolol on the growth of L. donovani promastigotes using defined medium were studied. Biosynthetically pulse labeling of promastigotes with [32P]-orthophosphate with or without experimental agents following SDS-PAGE and autoradiography was analyzed. Results: The growth of L. donovani promastigotes at 96 h culture was inhibited by 69%, 83, 52% and 95% with db-cAMP, epinephrine, isoproterenol and propranolol at 100 μM each, respectively in compared to control. Multiplication of parasite was stimulated by db-cGMP. The expression of lipophosphoglycan of the parasite was drastically affected in the following order with propranolol>epinephrine>cAMP>isoproterenol at 100 μM of each agent for 6 h exposure to the promastigotes. Conclusion: The growth of the parasite and the synthesis of lipophosphoglycan were significantly more inhibited by epinephrine or propranolol in a dose dependent manner than cAMP or isoproterenol. Keywords: cAMP; cGMP; epinephrine; Leishmania donovani; LPG; propronolol.